Solar fuels : materials, physics, and applications - Goodson, Theodore G. (CRC Press, 2017)
"Written for use as a text and reference for those interested in how new materials may be used to capture, store, and use solar energy for alternative energy resources in everyday life, Solar Fuels: Materials, Physics, and Applications discusses the fundamentals of new materials and the physical processes involved in their mechanisms and design. This book offers clear examples of current state-of-the-art organic and inorganic solar cell materials and devices used in the field, and includes experiments testing solar capability along with standardized examples. Last, but not least, it also gives a clear outline of the challenges that need to be addressed moving forward."--Publisher's description